2018
DOI: 10.1002/app.46399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of octa(epoxycyclohexyl) POSS on thermal, rheology property, and foaming behavior of PLA composites

Abstract: Foams of poly(lactic acid) (PLA)/octa(epoxycyclohexyl) polyhedral oligomeric silsesquioxanes (ePOSS) composite were prepared by melt‐mixing and solid‐state foaming methods. A systematic and accurate method was applied to evaluate the effects of epoxy‐based POSS on the structure of dispersion, thermal behavior, and rheological properties of PLA composites. The application of secondary electron–electron back‐scattered diffraction technique was used to observe the cellular micromorphology and micro‐phase dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Wei et al [ 91 ] investigated the impact of octa(epoxycyclohexyl) POSS (ePOSS) on the thermal, rheological, and foaming properties of PLA hybrids. Foams and composites PLA/ePOSS were prepared through melt mixing and solid‐state foaming methods, respectively.…”
Section: Pla/poss Composites/nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al [ 91 ] investigated the impact of octa(epoxycyclohexyl) POSS (ePOSS) on the thermal, rheological, and foaming properties of PLA hybrids. Foams and composites PLA/ePOSS were prepared through melt mixing and solid‐state foaming methods, respectively.…”
Section: Pla/poss Composites/nanocompositesmentioning
confidence: 99%
“…Hence this work reported that incorporation of POSS nanoparticles into PLA matrix enhanced the morphological properties such as dispersion level of plasticizer (PEG methyl ether grafted POSS) into PLA matrix. In a research work as F I G U R E 1 4 Rheological curves of the PLA/POSS composites [91] discussed above in Sections 4.1 and 4.2, Lee et al, [61] studied the effect of POSS on the morphological properties of PLA/POSS-PLA hybrids using the X-ray diffraction technique and by taking optical images using a digital camera. X-ray diffraction patterns of hydroxyl functionalized POSS and POSS-PLA hybrids were shown in Figure S10.…”
Section: Effect Of Poss On the Morphological Properties Of Pla/poss N...mentioning
confidence: 99%
“…The formation of branching structures in CPLA was favorable for crystallization nucleation and disadvantageous for crystallization growth, resulting in the generation of a large number of small spherocrystals in CPLA. 31 The cross-linked network formed by many small and dense crystals as physical cross-linking points could effectively improve the melt strength of PLA. It could be also found that the changes in crystallization properties observed by POM were consistent with the DSC test results.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, the crystalline region could not be biaxially stretched during the foaming process, which limited the cell growth to a certain extent. 40 On the other hand, the entanglements formed by branching and micro cross-linking structures could be served as the cross-linking points to enhance the melt viscosity of PLA and limit cell growth. 2 The cell size distribution of various PLA–SAG foams is shown in Figure 9.…”
Section: Resultsmentioning
confidence: 99%